PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA EKSPLOITASI SEKSUAL PADA ANAK DITINJAU MENURUT SOSIOLOGI - Winda Widya Sari; Beni Ahmad Saebani (Cahaya Ilmu Bangsa Institute, 2024)
This research examines legal protection for victims of sexual exploitation from the perspective of the sociology of Islamic law. Sexual exploitation is a violation of human dignity that causes physical, psychological and social impacts on the victim. Positive law in Indonesia, such as the Child Protection Law and the TPPO Law, provides a legal basis for victim protection, although its implementation often encounters obstacles. In the sociology of Islamic law, sexual exploitation is categorized as a serious violation of moral and spiritual values, with an emphasis on protection, restoration and respect for the victim's dignity. This research highlights the importance of an integrated approach between positive law and Islamic values ​​to increase protection for victims.